2017
DOI: 10.1080/14787210.2017.1309291
|View full text |Cite
|
Sign up to set email alerts
|

Nucleos(t)ide analogues for preventing HBV reactivation in immunosuppressed patients with hematological malignancies: a network meta-analysis

Abstract: Tenofovir and entecavir might be the most potent regimes in prevention of HBV reactivation for CHB infected patients with hematological malignancies undergoing chemotherapy or HSCT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 35 publications
0
8
0
1
Order By: Relevance
“…According to the guidelines for the management of HBV infection, HBV incipient screening and antiviral therapy are recommended to prevent HBV reactivation for patients receiving anti-cancer therapy, especially rituximab or hematopoietic stem cell transplantation. [ 25 , 26 ] In our study, 94% were tested early among the hematologic malignancy patients who had HBV testing. However, among the 153 patients with chronic HBV, only 40% had early antiviral therapy, likely because of less dynamic monitoring and antiviral therapy in a timely manner.…”
Section: Discussionmentioning
confidence: 96%
“…According to the guidelines for the management of HBV infection, HBV incipient screening and antiviral therapy are recommended to prevent HBV reactivation for patients receiving anti-cancer therapy, especially rituximab or hematopoietic stem cell transplantation. [ 25 , 26 ] In our study, 94% were tested early among the hematologic malignancy patients who had HBV testing. However, among the 153 patients with chronic HBV, only 40% had early antiviral therapy, likely because of less dynamic monitoring and antiviral therapy in a timely manner.…”
Section: Discussionmentioning
confidence: 96%
“…4 The present study found that several antitumor treatments, including TACE, RFA, MWA, PEI, and brachytherapy, were associated with HBV reactivation, which is associated with recurrence of HCC and OS, consistent with previous reports. [19][20][21][22][23] Combining antiviral treatment with conventional antitumor therapy is significantly associated with a reduced HBV reactivation. 24,25 When treating liver cancer (eg, by TACE), some patients developed hepatitis B flares, and their risk was reduced by the use of antiviral drugs.…”
Section: Discussionmentioning
confidence: 99%
“…In patients undergoing chemotherapy for various hematological malignancies, the reported incidence of HBVr is 32.08% to 60%. 30,31 The network meta-analysis by Zhang et al 10 compared the use of five antivirals for prophylaxis of HBVr in immunosuppressed patients with hematological malignancies and found superior efficacy for ETV (88%) and TDF (90%) when compared to LAM, ADV and TBV. Our meta-analysis focused on efficacy of HBVr prophylaxis specifically among allo-HSCT patients and analyzed data from ten studies in which 611 HR patients received prophylaxis.…”
Section: Discussionmentioning
confidence: 99%
“…Reference lists of, and citations to the articles eventually selected from the database searches, were also screened, as was the reference list of a related, recently published review. 10…”
Section: Methodsmentioning
confidence: 99%